New Insights on Environmental Occurrence of Pathogenic Fungi Based on Metagenomic Data from Brazilian Cerrado Biome - Costa,Flávia de Fátima (2022)
Abstract: Cerrado is the second largest biome in Brazil and majorly contributes to the country's grain production. Previous studies on soil metagenomics from the Cerrado revealed an outstanding microbial diversity. In this study, the abundance of pathogenic fungi was analyzed using metagenomic sequences of the Cerrado soils under native vegetation, and under agriculture with no-tillage and conventional tillage. In total, 128,627 sequences of fungi were identified, with 43,439 representing pathogenic fungi and were distributed as follows: native 17,301 (40%), no-tillage 13,780 (32%), and conventional tillage 12,358 (28%). We identified 41 pathogenic fungal species associated with human and animal infections. The data analysis revealed that the native soils had a higher relative abundance of fungal sequences, similar to pathogenic species sequences, in relation to the total eukaryotic sequences, than the conventional tillage and no-tillage treatments, which observed a reduction in fungal abundance because of anthropogenic activities.